(untitled) (CIPEEX, 2025)
Diabetes mellitus is a chronic endocrine-metabolic disease that is treated with medications that improve insulin production or action, or with exogenous insulin administration. Insulin must be stored and handled correctly in order to minimize application errors and ensure successful treatment and glucose control. With this in mind, the overall objective of this project is to assess the knowledge of medical students at the Evangelical University of Goiás regarding the handling and administration of insulin. The evaluation was carried out through a questionnaire, which aimed to assess errors and correct answers during patient guidance on insulin handling and administration. The results showed that the highest error rates were identified in sub-items related to the insulin application technique, the method of homogenization of NPH insulin, and possible application sites. On the other hand, the items with the highest accuracy were about contraindications for application in injured areas and the time to remove insulin from the refrigerator before application. The study revealed gaps in the students’ knowledge about insulin therapy, indicating the need to improve medical training and conduct new studies to address these deficiencies and thus increase the safety and effectiveness of diabetes mellitus treatment.